Improving anticorrosive properties of coatings based on zinc alloy TsAMSv4-1-2,5 doped with strontium - I. N. Ganiev; A. E. Berdiev; N. A. Aminova; S. J. Alikhonova (Омский научный вестник)
The results of an experimental study of the effect of strontium on the anodic behavior of the Tsam 4-1-2,5 alloy in the NaCl electrolyte medium are presented. It is shown that strontium additives reduce the corrosion rate of the initial alloy Tsamsv4-1-2.5 by 10 %. With an increase in concentration of chloride ion in the NaCl electrolyte, the corrosion and pitting potentials shift to the negative region, and the corrosion rate increases.